IMPLEMENTATION OF JIGSAW TECHNIQUE IN VOCABULARY ACQUISITION - Mujad Didien Afandi; Nailul Authar; Djuwari Djuwari; Tiyas Saputri; M Adrian Amien Anshari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Undeniably, the teacher-centered learning approach has long been abandoned. From the preliminary observation conducted in an elementary school located in Sidoarjo, Indonesia, it is found that most of the teachers still maintain their role as the knowledge providers. In consequence, the motivation and participation of the students are low. Therefore, this study was aimed at describing the implementation of jigsaw technique in vocabulary acquisition and obtaining the students’ perception of the implementation of the technique. Method. This qualitative study collected data using observation on English learning in a classroom to obtain a description about the implementation of jigsaw technique in vocabulary acquisition. Both field notes and a checklist will be used to collect the data concerning with the students’ activities when applying the jigsaw technique. Moreover, a questionnaire will be spread to the students to obtain the students’ perception of the implementation of the technique. Results and Discussion. The application of jigsaw technique in learning has followed an appropriate procedure. In addition, the students also showed positive perceptions of the Jigsaw Technique. This technique can create a positive learning environment, support Student-Centered Learning (SCL), support cooperative learning, and help students gain skills. Conclusion. The jigsaw technique is useful for learning English, especially in gaining understanding. Considering the benefits that students gain after applying the jigsaw technique to learn English, this technique is also recommended for improving other English language skills, such as listening, speaking, reading, and writing.